Importance of the Degree of Antigen Polymerization by Detoxification in Modulating the Immunogenicity of Acellular Pertussis Vaccine - Bae Cheon-Soon; Hong Sung-Sang; Ahn Sang-Jeom; Jang Yang-Suk; Hur Byung-Ki (Biotechnology and bioprocess engineering, 2005)
For the acellular pertussis vaccine with a high immunogenicity, the concentration, composition and characteristics of acellular pertussis antigens are the crucial points to be considered. Nevertheless, it has not been proved yet whether or not the polymerization degree, one of the characteristics of formalin-detoxified acellular pertussis antigens, has an influence on vaccine potency. Thus, in the present study, the correlations among detoxification conditions of acellular pertussis bulks, their polymerization degrees and their immunogenicities were examined. In addition, the relative importance of pertussis toxoid in vaccine immunogenicity was also investigated. Results show that a lower lysine concentration during detoxification induces highly-polymerized antigens, the immunogenicity has a great dependency on the polymerization degree of antigens, and also pertussis toxoid has a relatively stronger influence on the immunogenicity than other antigens. Accordingly, in the aspect of the potency of detoxified acellular pertussis vaccine, it can be demonstrated that the polymerization of antigens and its degree are the major factors affecting the immunogenicity along with a relatively high content of pertussis toxoid